2009
DOI: 10.1002/jcla.20306
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of PML‐RARα fusion transcript by real‐time PCR with a single primer pair

Abstract: Quantitative detection of minimal residual disease has prognostic value for some leukemias. Acute promyelocytic leukemia (APL) is characterized by the specific PML-RARalpha fusion gene from t(15;17). Added to three PML-RARalpha isoforms, alternative spliced forms of PML exons give rise to multiple isoforms even within a single patient. To date, multiple primer pairs for the detection of the various PML-RARalpha transcripts have been designed, potentially generating some nonspecific amplification products. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In any case, we emphasized the strict manipulation rules according to the Minimum Information for Publication of Quantitative Real-Time PCR Experiments (MIQE) guidelines [ 33 ]. The developed assay showed a sensitivity of 10 copies plasmid or 10 -4 RNA cell line dilution for PML-RARa, and this sensitivity is comparable to other studies [ 17 , 18 , 31 ]. Moreover the CVs of inter- and intra-assays were less than 3% for all the three transcripts, indicating that this assay is sensitive and reliable for PML-RARa detection.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In any case, we emphasized the strict manipulation rules according to the Minimum Information for Publication of Quantitative Real-Time PCR Experiments (MIQE) guidelines [ 33 ]. The developed assay showed a sensitivity of 10 copies plasmid or 10 -4 RNA cell line dilution for PML-RARa, and this sensitivity is comparable to other studies [ 17 , 18 , 31 ]. Moreover the CVs of inter- and intra-assays were less than 3% for all the three transcripts, indicating that this assay is sensitive and reliable for PML-RARa detection.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies reported that HybProbe-based RT-qPCR assays allow the detection of the PML-RARa fusion transcripts [ 30 , 31 ]. TaqMan-based RT-qPCR is the most appropriate method in clinical diagnostic laboratories considering cost, turnaround time, and assay performance [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Designation of primers for NUP98/PSIP1 fusion transcripts and RT‐PCR using AmpliTaq GOLD 360 Master Mix (Applied Biosystems, Foster City, CA, USA) were performed as described previously (6, 11).…”
Section: Methodsmentioning
confidence: 99%
“…Spectral karyotyping (SKY) and fluorescence in situ hybridization (FISH) We used SkyPaint kit (Applied Spectral Imaging, Migdal Ha'Emek, Israel) and NUP98 ⁄ D11Z1 dual color probe (SRL Inc., Tokyo, Japan) for SKY and FISH, respectively. Mix (Applied Biosystems, Foster City, CA, USA) were performed as described previously (6,11). RQ-PCR was carried out with N988F primer and PSIP1ex8R primer from exon 8 (5¢-TGGGTCTGCC TCTTGGTTTTGGA-3¢), Power SYBR Green PCR Master Mix, and 7900HT Fast Real-time PCR system (Applied Biosystems).…”
mentioning
confidence: 99%
“…The PML-RARα transcript for each patient was also measured by the real-time quantitative PCR (RQ-PCR) method that we recently established. 22 PCR for TdT detection was performed as previously described. 23 …”
Section: Methodsmentioning
confidence: 99%